Seed chemistry of Sophora chrysophylla (Mamane) in relation to diet of specialist avian seed predator Loxioides bailleui (Palila) in Hawaii - Banko, Paul C.; Wink, Michael (Journal of chemical ecology, 2002)
This study describes the chemical ecology of a tritrophic interaction among species endemic to the island of Hawaii, USA: a tree (Sophora chrysophylla: mamane), an endangered bird (Loxioides bailleui; palila), and moth larvae (Cydia spp.). Palila and Cydia both specialize on the seed embryos of mamane but avoid eating the seed coats. Palila actively seek out and feed mamane embryos and Cydia larvae to their nestlings. Because mamane embryos contain potentially toxic levels of alkaloids, including broadly toxic quinolizidine alkaloids, and because insects often sequester alkaloids from their food plants, we focus on the questions of why palila forage upon mamane embryos and why they supplement their diet with Cydia larvae. Our data show that mamane embryos contain high amounts of potentially toxic alkaloids, but are well balanced nutritionally and contain lipids, carbohydrates, proteins, amino acids, and minerals at levels that are likely to be sufficient for maintenance and breeding. Mamane seed coats contain lower levels of alkaloids and nutrients, somewhat higher levels of phenolics, and much higher levels of nondigestible fiber. Taken together, these results suggest that palila have evolved tolerance to high levels of alkaloids and that they forage upon embryos primarily because of their availability in the habitat and high nutritional reward. Our data also suggest that Cydia are used by palila because they are readily accessible, nontoxic, and nutritious; the larvae apparently do not sequester alkaloids while feeding upon mamane seeds. Our results are interpreted with respect to the likelihood of current and historical coadaptive responses in this ecologically isolated and simplified island setting.
Gesehen am 05.10.2017